Factors Associated With Physical and Psychological Health Outcomes Among Inmate Women in Portugal - Alves, Joana (Women & criminal justice, 2024)
This study aims to identify the variables associated with self-reported physical and psychological symptoms and the perceived health status of inmate women in Portugal. Data collection took place in two female Portuguese prisons and participated in the study 232 women. Physical symptomatology was associated with having children, physical abuse in childhood, a higher number of chronic diseases, and anxiety. Older women, the experience of sexual abuse, and chronic diseases were associated with a worse perception of physical health. Psychological symptoms were higher in women that reported substance abuse before prison, chronic diseases, anxiety, and depression. Finally, a combination of the prior variables (sexual abuse, anxiety, and depression) and three additional variables (lower education level, not having contact with mental health services before prison, and being already sentenced) was associated with worse perceptions of mental health conditions. These findings can be used as a platform for future research, as well as a tool for prison policy regarding the particular gender health needs of inmate women.